Predictors of Outcome of Aneurysmal Subarachnoid hemorrhage - Bishokarma, Suresh; Shrestha, Shikher; Rijal, Suman; Karki, Anjali; Shrestha, Sunita; Thulung, Suraj (Nepal Journal of Neuroscience, 2022)
Introduction: Aneurysmal Subarachnoid Hemorrhage (aSAH) is a devastating condition with high mortality and morbidity. Significant factors influencing the prognosis of aneurysmal subarachnoid hemorrhage (SAH) include the severity at presentation of the disease and delayed cerebral ischemia (DCI). Methods: This is a prospective study conducted in Upendra Devkota Memorial National Institute of Neurological and Allied Sciences (UDM-NINAS), Bansbari, Kathmandu, Nepal among patients who underwent clipping of aneurysm for subarachnoid hemorrhage. Various clinical and radiological prognostic factors were registered on admission and during the intensive care stay. Outcome was recorded. GOS>3 was considered good outcome and GOS ≤3 was considered poor outcome. Results: Seventy-two patients with ruptured aneurysm were surgically clipped. Good outcome was observed in 51 (70.83%) patients while poor outcome was seen among 21 (29.17%) patients including death among 16 (22.2%) patients. In univariate analysis, WFNS>2, Fisher grade >2, EVD placement for hydrocephalus and delayed cerebral ischemia (DCI) were found to have statistically significant in poor outcome. On Multivariate logistic regression model showed delayed cerebral ischemia was statistically significant predictor of poor outcome at p= 0.032 (OR= 7.34; 95% CI=1.280 to 17.702). Conclusion: WFNS >2, Fisher grade>2, EVD placement and DCI were found to have statistical significance in poor outcome while only DCI was an independent predictor of poor outcome following aneurysmal Subarachnoid Hemorrhage (aSAH).